The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1074/jbc.m707037200
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrimeric G Protein βγ Subunits Stimulate FLJ00018, a Guanine Nucleotide Exchange Factor for Rac1 and Cdc42

Abstract: We previously reported that G␤␥ signaling regulates cell spreading or cell shape change through activation of a Rho family small GTPase, suggesting the existence of a G␤␥-regulated Rho guanine-nucleotide exchange factor (RhoGEF). In this study we examined various RhoGEF clones, found FLJ00018 to be a G␤␥-activated RhoGEF, and investigated the molecular mechanism of G␤␥-induced activation of Rho family GTPases. Co-expression of the genes for FLJ00018 and G␤␥ enhanced serum response element-mediated gene transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
64
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 42 publications
(47 reference statements)
6
64
0
Order By: Relevance
“…12,13) On the other hand, wortmannin does not attenuate FLJ00018-induced SRE-dependent gene transcription. 6) These results suggested that the lipid requirement of FLJ00018 differs from that of KIAA1415/P-Rex1.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…12,13) On the other hand, wortmannin does not attenuate FLJ00018-induced SRE-dependent gene transcription. 6) These results suggested that the lipid requirement of FLJ00018 differs from that of KIAA1415/P-Rex1.…”
mentioning
confidence: 58%
“…Rabbit anti-Gβ antibody was pre-pared as described previously and used to detect Gβ. 6) Cell Culture, Transfection, and Immunoblot Analysis HEK293 cells were grown in Dulbecco's modified essential medium (DMEM) supplemented with 10% fetal bovine serum at 37°C. Transient transfection was performed using LipofectAMINE Plus according to the manufacturer's instructions (Life Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study FLJ00018 was activated by direct interaction with a G␤␥ subunit (7), and the activation was attenuated through interaction with cytosolic actin (8). In this study we also discovered another FLJ00018 activation mechanism by threonine phosphorylation at 680 through the EGFR/Ras/ MAPK pathway.…”
Section: Discussionmentioning
confidence: 71%
“…Is Activated by ␤ 1 -Adrenergic Receptor Stimulation through a G␤␥-dependent and -independent Pathway-We previously reported that FLJ00018 was activated by G␤␥ and m2 muscarinic acetylcholine receptor stimulation (7). To examine whether FLJ00018 is activated by stimulation of other GPCRs, we used a ␤-adrenergic receptor, ␤ 1 -AR, that is known to couple with multiple signaling pathways via G s protein.…”
Section: Flj00018mentioning
confidence: 99%
See 1 more Smart Citation